Nobody's princess - Friesner, Esther M. (Random House, 2007)
Determined to fend for herself in a world where only men have real freedom, headstrong Helen, who will be called queen of Sparta and Helen of Troy one day, learns to fight, hunt, and ride horses while disguised as a boy, and goes on an adventure throughout the Mediterranean world.